Health and fitness trends in Southern Europe for 2023: A cross-sectional survey - Alexios Batrakoulis; Oscar L Veiga; Susana Franco; Ewan Thomas; Antonios Alexopoulos; Manel Valcarce-Torrente; Rita Santos-Rocha; Fatima Ramalho; Andrea Di Credico; Daniela Vitucci; Liliana Ramos; Vera Simões; et al. (AIMS Press, 2023)
The physical activity, exercise and wellness sector is rapidly growing and seems to be an exciting field for business and professional development with great potential globally. The purpose of this observational and cross-sectional study was to determine the most popular health and fitness trends in Southern Europe for the first time, including data from Italy, Spain, Portugal, Greece and Cyprus, and to investigate any potential differences in this area compared to the Pan-European and global fitness trends for 2023. A national online survey was conducted in five Southern European countries, using the methodology of similar regional and worldwide surveys conducted by the American College of Sports Medicine since 2007. In total, a web-based questionnaire was sent to 19,887 professionals who worked in the Southern European physical activity, exercise and wellness sector. A total of 2645 responses were collected from five national surveys with an overall mean response rate of 13.3%. The ten most important fitness trends in Southern Europe for 2023 were personal training, licensure for fitness professionals, exercise is medicine, employing certified fitness professionals, functional fitness training, small group training, high-intensity interval training, fitness programs for older adults, post-rehabilitation classes and body weight training. The present findings are aligned with those reported for the European and worldwide fitness trends.